2019
DOI: 10.1108/jsbed-08-2018-0258
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial actions: implications for firm performance

Abstract: Purpose The purpose of this paper is to investigate different types of investment actions undertaken by entrepreneurial firms to determine how these actions influence performance. Specifically, the effects of entrepreneurial action with regards to investments in human capital, the capabilities of the firm and the competitive dynamics of the business relative to other firms are examined. These actions are examined in conjunction with the offering of products, services or both, to determine the benefits of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 101 publications
(102 reference statements)
0
3
0
2
Order By: Relevance
“…Organizations around the globe recognize that performance is an important element for business growth and sustainability (AlNuaimi et al , 2020; Epstein and Roy, 2001; Sproul et al , 2019). Prior research has identified important aspects of firm performance, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Organizations around the globe recognize that performance is an important element for business growth and sustainability (AlNuaimi et al , 2020; Epstein and Roy, 2001; Sproul et al , 2019). Prior research has identified important aspects of firm performance, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…primary, junior-senior high school; n = 67.48%), whereas the remainder have a university education background. Despite the notion that higher education is expected to leverage better entrepreneurial outcomes (Sproul et al , 2019), it may also be possible that general human capital has no effect on firms’ economic outcomes (i.e. growth, performance) as is indicated in prior studies (Bosma et al , 2004; El Shoubaki et al , 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Kedua, keterampilan manajerial menjadi bagian penting dari kompetensi wirausaha. Keterampilan ini melibatkan kemampuan untuk merencanakan bisnis, mengambil keputusan yang berdasarkan analisis yang baik, mengelola risiko, mengatur waktu dengan efektif, dan mengelola proyek bisnis dengan baik (Uyargil, C., Karadeniz, E. E., & Abimbola, 2019). Selain itu, kemampuan untuk memimpin dan mengelola tim juga merupakan bagian dari kompetensi manajerial yang penting dalam konteks wirausaha.…”
Section: Kajian Pustakaunclassified
“…Keterampilan berpikir analitis: Pendidikan kewirausahaan membantu individu mengembangkan keterampilan berpikir analitis yang penting dalam menghadapi masalah dan mengambil keputusan yang berdasarkan data (Uyargil, C., Karadeniz, E. E., & Abimbola, 2019). Mereka belajar untuk menganalisis situasi, mengidentifikasi peluang, mengevaluasi risiko, dan mengambil langkah-langkah strategis.…”
Section: Hasil Dan Pembahasanunclassified